ANALYZING THE UTILIZATION OF ACADEMIC INFORMATION SYSTEM TECHNOLOGY IN SERVICE PROVISION - Eko Bambang Murdiansyah; Farid Wajdi; Rais Abin (Edutainment : Jurnal Ilmu Pendidikan dan Kependidikan, 2024)
This study aims to determine and analyze the use of SIAKAD, inhibiting and supporting factors for the use of SIAKAD, and the impact of the use of academic information system technology in providing academic services to students of Sembilanbelas November University Kolaka. This study uses a qualitative descriptive method, the research informants are 12 permanent employees, 30 students of Sembilanbelas November University Kolaka. Data collection was carried out using observation, interview, and documentation instruments. The results of the study indicate that the use of SIAKAD has not been maximized, there are still many obstacles in its implementation, namely the network system often experiences disruptions, inhibiting factors include; weak network, unavailability of computer facilities in accessing the academic portal/siakad online in each building and supporting factors include; availability of adequate access devices, both hardware, software and networks, financial support from the leadership, and the impact of SIAKAD is widely felt, including being able to see the requested data, especially academic data, for students themselves it becomes faster because it is connected to the internet, efficient because they do not need to come to campus but can be done at home or via the internet wherever they are.